High resolution analysis of the chromatin landscape of the IgE switch region in human B cells. - Sandeep Dayal; Jakub Nedbal; Philip Hobson; Alison M Cooper; Hannah J Gould; Martin Gellert; Gary Felsenfeld; David J Fear (PLoS ONE)
Antibodies are assembled by a highly orchestrated series of recombination events during B cell development. One of these events, class switch recombination, is required to produce the IgG, IgE and IgA antibody isotypes characteristic of a secondary immune response. The action of the enzyme activation induced cytidine deaminase is now known to be essential for the initiation of this recombination event. Previous studies have demonstrated that the immunoglobulin switch regions acquire distinct histone modifications prior to recombination. We now present a high resolution analysis of these histone modifications across the IgE switch region prior to the initiation of class switch recombination in primary human B cells and the human CL-01 B cell line. These data show that upon stimulation with IL-4 and an anti-CD40 antibody that mimics T cell help, the nucleosomes of the switch regions are highly modified on histone H3, accumulating acetylation marks and tri-methylation of lysine 4. Distinct peaks of modified histones are found across the switch region, most notably at the 5' splice donor site of the germline (I) exon, which also accumulates AID. These data suggest that acetylation and K4 tri-methylation of histone H3 may represent marks of recombinationally active chromatin and further implicates splicing in the regulation of AID action.